COP21 and the Paris Agreement: a diplomacy masterclass in search of greater climate ambition - Lázaro, Lara (Papeles de Europa, 2016)
Many key elements that led to the Copenhagen Accord have evolved in the past six years. Increased scientific evidence, updated economic analysis on the consequences of climate change, technological advances, developments in the renewable energy sector and transformations in climate governance have created a narrow window of opportunity through which the Paris Agreement emerged. Some of these key changes, the results of COP21 and the challenges ahead are critically analysed. The analysis concludes that the diplomatic success that culminated in the adoption of the Paris Agreement provides the world with a new global climate governance framework that contains valuable elements in the fight against climate change. However, current mitigation commitments will overshoot the 2ºC limit by around one degree. Therefore more needs to be done and work has to start in earnest now if we are to avoid the worst consequences of a changing climate. The task at hand is herculean as solving the climate problem requires profoundly transforming productive systems and consumption patterns.
Keywords: Climate change; COP21; INDCs and; decarbonisation